2016
DOI: 10.3389/fphar.2016.00385
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Sulfide in Renal System

Abstract: Hydrogen sulfide has gained recognition as the third gaseous signaling molecule after nitric oxide and carbon monoxide. This review surveys the emerging role of H2S in mammalian renal system, with emphasis on both renal physiology and diseases. H2S is produced redundantly by four pathways in kidney, indicating the abundance of this gaseous molecule in the organ. In physiological conditions, H2S was found to regulate the excretory function of the kidney possibly by the inhibitory effect on sodium transporters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 114 publications
(161 reference statements)
2
89
0
4
Order By: Relevance
“…The enzyme D-amino acid oxidase constitutes an additional enzymatic pathway for H 2 S production and is highly expressed in mammalian kidneys (Shibuya et al, 2013). In mammals, endogenous H 2 S is proposed to be important for normal kidney function (Lobb et al, 2015) and H 2 S has been shown to increase glomerular filtration rate (Xia et al, 2009) and salt excretion by inhibition of Na + /K + -ATPase (Ge et al, 2014), and to suppress renin release (Cao and Bian, 2016). Given that H 2 S is an ancient vasoregulatory molecule across multiple vertebrate clades (Dombkowski et al, 2004), our data indicate that H 2 S could also have a similar regulatory role in the renal function of turtles.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme D-amino acid oxidase constitutes an additional enzymatic pathway for H 2 S production and is highly expressed in mammalian kidneys (Shibuya et al, 2013). In mammals, endogenous H 2 S is proposed to be important for normal kidney function (Lobb et al, 2015) and H 2 S has been shown to increase glomerular filtration rate (Xia et al, 2009) and salt excretion by inhibition of Na + /K + -ATPase (Ge et al, 2014), and to suppress renin release (Cao and Bian, 2016). Given that H 2 S is an ancient vasoregulatory molecule across multiple vertebrate clades (Dombkowski et al, 2004), our data indicate that H 2 S could also have a similar regulatory role in the renal function of turtles.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent publications have revealed that H 2 S is synthesized in mammalian tissues, and freely travels through cell membranes. H 2 S acts independently of any specific transporters, and it has a number of biological effects on various systems (Meng et al, ; Cao and Bian, ; Feliers et al, ; Ianaro et al, ; Katsouda et al, ; Cheng et al, ). Nowadays, H 2 S is regarded as the third endogenous gasotransmitter followed by NO and CO (Hine et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both CBS and CSE are critical for H 2 S generation in the kidney (5,12). Our data showed that the suppression of the endogenous H 2 S production by the inhibition of CBS and CSE in mice caused increased urine output, decreased urine osmolality, and impaired urine concentration in response to water deprivation.…”
Section: Discussionmentioning
confidence: 64%
“…CBS catalyzes homocysteine derived from methionine to produce cystathionine, which is converted into L-cysteine by CSE. L-Cysteine can be used as a substrate by both CBS and CSE to generate H 2 S. CSE can also catalyze H 2 S production by the conversion of homocysteine into homolanthionine (4,5), CBS is critical in the development of neonatal mice. Moribund CBS knockout (cbs 2/2 ) mice exhibit severe fibrosis and neutrophil invasion.…”
mentioning
confidence: 99%